A Comparative Review of Neutrophil Extracellular Traps in Sepsis - Li, Ronald H. L.; Tablin, Fern (Frontiers in Veterinary Science, 2018)
Sepsis is the leading cause of critical illness and mortality in human beings and animals. Neutrophils are the primary effector cells of innate immunity during sepsis. Besides degranulation and phagocytosis, neutrophils also release neutrophil extracellular traps (NETs), composed of cell-free DNA, histones and antimicrobial proteins. Although NETs have protective roles in the initial stages of sepsis, excessive NET formation has been found to induce thrombosis and multiple organ failure in murine sepsis models. Since the discovery of NETs nearly a decade ago, many investigators have identified NETs in various species. However, many questions remain regarding the exact mechanisms and fate of neutrophils following NET formation. In humans and mice, platelet-neutrophil interactions via direct binding or soluble mediators seem to play an important role in mediating NET formation during sepsis. Preliminary data suggest that these interactions may be species dependent. Regardless of these differences, there is increasing evidence in human and veterinary medicine suggesting that NETs play a crucial role in the pathogenesis of intravascular thrombosis and multiple organ failure in sepsis. Because the outcome of sepsis is highly dependent on early recognition and intervention, detection of NETs or NET components can aid in the diagnosis of sepsis in humans and veterinary species. In addition, the use of novel therapies such as deoxyribonuclease and non-anticoagulant heparin to target NET components shows promising results in murine septic models. Much work is needed in translating these NET-targeting therapies to clinical practice.